Correction of frameshift mutations in the atpB gene by translational recoding in chloroplasts of Oenothera and tobacco. Issue 5 (9th February 2021) - Malinova, Irina; Zupok, Arkadiusz; Massouh, Amid; Schöttler, Mark Aurel; Meyer, Etienne H; Yaneva-Roder, Liliya; Szymanski, Witold; Rößner, Margit; Ruf, Stephanie; Bock, Ralph; Greiner, Stephan
Abstract : Analysis of spontaneous Oenothera mutant and various transplastomic tobacco lines confirms operation of ribosomal frameshifting in chloroplasts. Abstract: Translational recoding, also known as ribosomal frameshifting, is a process that causes ribosome slippage along the messenger RNA, thereby changing the amino acid sequence of the synthesized protein. Whether the chloroplast employs recoding is unknown. I-iota, a plastome mutant of Oenothera (evening primrose), carries a single adenine insertion in an oligoA stretch [11A] of the atpB coding region (encoding the β-subunit of the ATP synthase). The mutation is expected to cause synthesis of a truncated, nonfunctional protein. We report that a full-length AtpB protein is detectable in I-iota leaves, suggesting operation of a recoding mechanism. To characterize the phenomenon, we generated transplastomic tobacco lines in which the atpB reading frame was altered by insertions or deletions in the oligoA motif. We observed that insertion of two adenines was more efficiently corrected than insertion of a single adenine, or deletion of one or two adenines. We further show that homopolymeric composition of the oligoA stretch is essential for recoding, as an additional replacement of AAA lysine codon by AAG resulted in an albino phenotype. Our work provides evidence for the operation of translational recoding in chloroplasts. Recoding enables correction of frameshift mutations and can restore photoautotrophic growth in the presence of a mutation that otherwise would be lethal.